Rancang Bangun Pencarian File Multimedia Berbasis Web Menggunakan Standar Scorm 2004 - Perdana, Hevea Bori; Hariadi, Bambang; Sagirani, Tri (Jurnal JSIKA, 2012)
In an organization of education, training and learning is an activity that is very important. Currently, training and learning can be replaced by using information technology that is now growing rapidly in such regardless of who the perpetrator, without limitation of place and time. In the terminology of development of information technology training and learning form thus known by the term e-Learning. E-Learning has become a strategy and solutions for successful organizations in the world in order to manage and update their students´ learning. Based on the above issues, then built an interactive multimedia online learning system. In this thesis, an interactive learning system (E-Learning) apply the reference standard SCORM 2004.   Keyword : SCORM 2004, SCO, E-Learning, Multimedia